1981
DOI: 10.1017/s0022029900021518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding potassium iodate to milk before UHT treatment: I. Reduction in the amount of deposit on the heated surfaces

Abstract: Additions of potassium iodate to milk at 0-05 and 0 -l DIM (10 and 20 ppm) before UHT treatment markedly reduced the rate at which pressure built up during processing. This permitted the use of longer processing times before unacceptable pressures were reached in the heat exchangers. Iodate reduced the amount of protein deposited, particularly in the higher temperature sections of the plant, but had no effect on the deposition of minerals. The more compact nature of the highly mineral deposits offered less res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 29 publications
5
31
0
Order By: Relevance
“…5c and 5d), giving rise to a difference in the formation rate of aggregates. with the results of Skudder et al (14) who found that a reduction of free sulfydryl groups in milk markedly reduced This is in agreement with the findings that bulk reactions are rate limiting in the fouling process (15). Arnebrant et the amount of protein adsorbed.…”
Section: Dynamic Light Scattering (Dls) Is At Ph 7 (20)supporting
confidence: 91%
“…5c and 5d), giving rise to a difference in the formation rate of aggregates. with the results of Skudder et al (14) who found that a reduction of free sulfydryl groups in milk markedly reduced This is in agreement with the findings that bulk reactions are rate limiting in the fouling process (15). Arnebrant et the amount of protein adsorbed.…”
Section: Dynamic Light Scattering (Dls) Is At Ph 7 (20)supporting
confidence: 91%
“…Fouling not only results in higher operating costs but has an adverse effect on environment also (Brinkmann, 1986;Graßhoff, 1997;Sandu & Singh, 1991;. Various factors influencing the deposit formation in UHT processing include fore-warming of milk (Bell & Senders, 1944;Lyster, 1965;Burton, 1966;Mottar & Moermans, 1988;Patil & Reuter, 1986a, 1986b, prepasteurization (Lalande, Tissier, & Corrieu, 1984), pH of milk (Burton, 1966;Gordon, Hankinson, & Carver, 1968;Gynning, Thome, & Samuelsson, 1958;Kastanas, Lewis, & Grandison, 1995;Patil & Reuter, 1988;Skudder, Brooker, Bonsey, & Alvarez Guerrero, 1986), air content (Jeurnink, 1995;Tirumalesh, Rao, & Jayaprakash, 1997), surface material (Foster, Britten, & Green, 1989;Foster & Green, 1990;Jeurnink, Verheul, Cohen, & de Kruif, 1996;Sharon & Fuller, 1994;Visser, Jeurnink, Schraml, Fryer, & Delplace, 1997) total solids, age of milk, season, addition of oxidizing agents (iodate, H 2 O 2 , dichromate) (Marshall, 1986;Skudder, Thomas, Pavey, & Perkin, 1981), addition of free fatty acids (Al-roubale & Burton, 1979), addition of phosphates (Burdett, 1974), etc. A number of attempts have been made earlier to cope with the problem of fouling which include design of fouling resistant equipment i.e.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Oxidation of SH groups by iodate reduces deposit formation during ultrahigh-temperature (UHT) treatment of milk. 13 Mottram et al 14 demonstrated that changes in thē avour threshold of disulphide compounds such as bis-2-furanylmethyl disulphide may be due to SH± disulphide interchange with proteins.…”
Section: Introductionmentioning
confidence: 99%